2014
DOI: 10.2350/13-02-1305-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Diagnosis of Achondrogenesis Type 2 in a Fragmented Fetus: Case Report and Evidence-Based Differential Diagnostic Approach in the Early Midtrimester

Abstract: As a group, lethal genetic skeletal disorders (GSDs) usually result in death within the perinatal period. Because lethal GSDs are often ultrasonographically detectible by early midtrimester, dilation and evacuation (D&E) is the method of choice for elective termination of pregnancy in many institutions. However, because the diagnosis of the lethal GSDs relies heavily upon radiologic examination of fetal remains, reaching an accurate diagnosis in this setting can be challenging. We report an autopsy case of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Moreover, revealed that the fetus showed heterozygous mutation in the COL2A1 gene [c.1358G>A transition (Gly453Asp) in exon 19. 10 Superti-Furga et al to state that a distinction between ACG-1A, 1B ACG, and ACG-2 on clinical grounds is difficult. 13 More details that almost normal hands are seen in ACG-2, whereas in ACG-1A and ACG-1B showed that the hands are evidently shortened.…”
Section: Achondrogenesis Type 2 In a Fragmented Fetusmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, revealed that the fetus showed heterozygous mutation in the COL2A1 gene [c.1358G>A transition (Gly453Asp) in exon 19. 10 Superti-Furga et al to state that a distinction between ACG-1A, 1B ACG, and ACG-2 on clinical grounds is difficult. 13 More details that almost normal hands are seen in ACG-2, whereas in ACG-1A and ACG-1B showed that the hands are evidently shortened.…”
Section: Achondrogenesis Type 2 In a Fragmented Fetusmentioning
confidence: 99%
“…Elective termination by dilation and evacuation (D and E) was performed at a 15 4/7 weeks. 10 Prenatal, post mortem, radiography and histology examination of fragmented fetus in ACG-2 presented in Table 4. The radiographs and histology of the long bone in ACG-2 presented in Figure 9.…”
Section: Achondrogenesis Type 2 In a Fragmented Fetusmentioning
confidence: 99%